Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Association between indoor PM2.5 components and accelerated biological aging in schizophrenia patients: Evidence from multi-omics mechanisms - Rubing Pan; Xingxu Yi; Yanlong Xu; Jian Song; Weizhuo Yi; Jintao Liu; Rong Song; Xuanxuan Li; Li Liu; Jiajun Yuan; Ning Wei; Yuxing Huang; et al. (Journal of Hazardous Materials, 2024)

Comparison of the short- and long-term effects of zinc ions on the anaerobic mesophilic co-digestion of food waste and waste activated sludge: Digester performance, antibiotic resistance gene reduction and the microbial community - Bao-Shan Xing; Yi-Meng Su; Yu-Lin Fu; Yi-Fan Wu; Chen-Hao Yan; Xiaochang C. Wang; Yu-You Li; Rong Chen (Journal of Hazardous Materials, 2024)

Multiple NADPH-cytochrome P450 reductases from Lycoris radiata involved in Amaryllidaceae alkaloids biosynthesis - Yuqing Wu; Yifeng Zhang; Haitong Fan; Jie Gao; Siyu Shen; Jifan Jia; Rong Liu; Ping Su; Yating Hu; Wei Gao; Dan Li (Plant Molecular Biology, 2024)

Enhancing effect of conductive materials and rumen microorganisms on the anaerobic digestion performance of a real traditional Chinese medicine wastewater - Han Gao; Xiang-Lin Chang; Su Li; Rong Chen; Yu-You Li; Bao-Shan Xing (Journal of Water Process Engineering, 2024)

Enhanced photocatalytic hydrogen evolution via yolk–heteroshell TiO2@TiO2/SiO2 nanoreactor with confined Pt nanoparticles - Haimei Liu; Min Shi; Rong Yang; Ye Wang; Haiyan li; Qiying Su; Tao Wang; Sheng Wang (Chemical Engineering Journal, 2024)

Effects of socioeconomic status and regional inequality on the association between PM2.5 and its components and cardiometabolic multimorbidity: A multicenter population-based survey in eastern China - Zhiqian Cui; Xinxu Yi; Yuxin Huang; Ming Li; Zichen Zhang; Lingmei Kuang; Rong Song; Jintao Liu; Rubing Pan; Weizhuo Yi; Xiaoyu Jin; Jian Song; et al. (Science of The Total Environment, 2024)

Impaired thyroid hormone sensitivity exacerbates the effect of PM2.5 and its components on dyslipidemia in schizophrenia - Jintao Liu; Yinguang Fan; Jian Song; Rong Song; Xuanxuan Li; Li Liu; Ning Wei; Jiajun Yuan; Weizhuo Yi; Rubing Pan; Xiaoyu Jin; Jian Cheng; et al. (Science of The Total Environment, 2024)

Microbiomic and metabolomic dynamics in chrysanthemum waste at different fermentation stages - Yiyan Cui; Xinyan Ma; Miao Yu; Su Peng; Zhimei Tian; Min Song; Dun Deng; Zhichang Liu; Ting Rong; Zhenming Li; Xianyong Ma (Food Bioscience, 2024)

Mitigating nitrite inhibition in Klebsiella strain denitrification: Stimulating endogenous driving force with microscale zero-valent iron - Wen-ying Cao; Kuang-di Xu; Su Zhang; Si-jia Li; Yi-cheng Yuan; Jing-xuan Lu; Lei Yu; Shao-hua Zhou; Jun-ting Gan; Quan Wang; Rong-ping Chen; Ke Yin (Chemical Engineering Journal, 2024)

Chemical constituents from Croton lauioides Radcl.-Sm. & Govaerts and their chemotaxonomic significance - Jia-Xin Hu; Qian Liang; Li-Lin Xiao; Rong-Lin Jia; Xiao-Min Su; Wen-Hui Xu (Biochemical Systematics and Ecology, 2024)

Influenza A Virus PB1-F2 Induces Affective Disorder by Interfering Synaptic Plasticity in Hippocampal Dentate Gyrus - Saiying Wang; Haijun Zhang; Rui Liu; Peijun Han; Qi Yang; Caiyan Cheng; Yue Chen; Zheng Rong; Chang Su; Fei Li; Gaofei Wei; Minggao Zhao; et al. (Molecular Neurobiology, 2024)

Cloning and functional identification of anthocyanin synthesis-regulating transcription factor AaMYB4 in Aeonium arboreum Webb & Berthel ‘Halloween’ - Rong Zhao; Su-Hua Li; Hao-Zhang Han; Li-Hua Zhang; Fang Wang; Nan Zhang (Brazilian Journal of Botany, 2024)

High-risk ARGs (HRA) Chip: A high-throughput qPCR-based array for assessment of high-risk ARGs from the environment - Huan-Qin Li; Mei-Rong Xu; Xin-Li An; Hu Liao; Li-Juan Li; Wei Li; Jian-Qiang Su (Water Research, 2024)

A pooled mycoviral resource in a strain of Rhizoctonia solani are regulators of fungal virulence - Ya Rong Wang; Jia En Su; Zhi Juan Yang; Jie Zhong; Xiao Gang Li; Yi Chen; Jun Zi Zhu (Pesticide Biochemistry and Physiology, 2024)

Strong ground motion characteristics of the 2022 MW 6.6 Luding earthquake and regional variability in ground motion among three earthquake areas in Sichuan, Southwest China - Bin Zhang; Xiaojun Li; Yanxiang Yu; Xiaojian Lu; Mianshui Rong; Su Chen; Zhao An; Zhenghui Xiong (Bulletin of Earthquake Engineering, 2024)

Mercury supply limits methylmercury production in paddy soils - Huan Zhong; Yao Su; Xinda Wu; Luís Nunes; Chengjun Li; Yunyun Hao; Yu-Rong Liu; Wenli Tang (Science of The Total Environment, 2024)

Metabolome and transcriptome reveal high abundance of bioactive substances in albino jujube fruit as potential function food - Yang Wang; Yong Huang; Panhui Song; Xuemei Peng; Xinyu Li; Rong Su; Hui Zhang; Lijin Lin; Hui Xia; Qunxian Deng (Food Bioscience, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

Experimental and Numerical Study of Suspended Inter-Array Cable Configurations for Floating Offshore Wind Farm - Di-Rong Li; Yu-Shiou Su; Ray-Yeng Yang (Journal of Marine Science and Engineering, 2024)
The present study evaluates the feasibility of using a fully suspended inter-array cable system for an offshore wind farm. It includes both numerical simulations and a scaled-down experiment, conducted at a 1:49 scale, to validate the numerical results. To achieve the goal, a 15 MW floating offshore wind turbine (FOWT) and a floating offshore substation (FOSS) are involved to simulate the wind farm array. This study incorporates the 50-year return period conditions of the Taiwan Hsinchu offshore area, which has a water depth of about 100 m, to validate the specifications related to the platform motion and mooring line tension. Additionally, an analysis of the tension, curvature, and fatigue damage of the dynamic cable system is discussed in this research. Because a fully suspended cable is a relatively new concept and may be more frequently considered in a deeper water depth area, numerical simulation software Orcina Orcaflex 11.4 has been chosen to conduct the fully coupled simulation, determining whether the fully suspended cable system could effectively withstand the challenges posed by extreme sea conditions. This is due to the reason that a fully suspended cable would occupy a larger space in the ocean, which may pose a risk by influencing the navigation of the vessels. Therefore, the cable laying depth under normal sea states is also discussed to evaluate the influence over vessel navigation. This study also collects the long-term environmental data from the Central Weather Bureau, Taiwan, to calculate the accumulative cable fatigue damage under different sea states. To integrate the results, this research applies fitness parameters to evaluate the feasibility of each cable configuration. Covering the cable performance under extreme sea states and regular operating sea states offers valuable insights for applications in ocean engineering.

Long-Term Spatiotemporal Characteristics of Ulva prolifera Green Tide and Effects of Environmental Drivers on Its Monitoring by Satellites: A Case Study in the Yellow Sea, China, from 2008 to 2023 - Yating Zhan; Zhongfeng Qiu; Yujun Wang; Yiming Su; Yin Li; Yanmei Cui; Shuai Qu; Peng Wang; Xin Rong (Journal of Marine Science and Engineering, 2024)
Ulva prolifera (U. prolifera) green tide outbreaks have occurred in the Yellow Sea of China for many years, causing serious losses to marine ecology and the marine economy. The monitoring and tracking of U. prolifera green tide is a crucial aspect of marine ecological disaster prevention and control management. This paper aims to investigate the spatiotemporal distribution changes in U. prolifera green tide in the Yellow Sea throughout its life cycle. A survey of the Yellow Sea from 2008 to 2023 was conducted using multi-source remote sensing images. Long-term monitoring and analysis of U. prolifera revealed the evolution process of the green tide, including the early development, outbreak, decline, and extinction stages, considering time, space, and frequency of occurrence. Additionally, this study examined peak coverage change patterns over the past 16 years and analyzed the influence of environmental factors such as sea surface temperature and sea surface wind field on the development of U. prolifera. The research results serve as a valuable reference for the monitoring, early warning, and scientific prevention and control of U. prolifera green tide in the Yellow Sea, as well as other similar marine disaster areas.

The double-edged effects of La2O3 and CeO2 on the performance of high-rate anaerobic sludge bed reactors and microbial mechanisms - Kai Su; Lin-xiao Li; Zhuo Zeng; Xue Yang; Tao Lei; Han Zhang; Qin Wang; Rong Cao (Process Safety and Environmental Protection, 2024)

A new strategy of using periphyton to simultaneously promote remediation of PAHs-contaminated soil and production of safer crops - Su-Xin Li; Xiao-Rong Gao; Jun Yi; Ling-Yun Jia; Jun Ren (Environmental Research, 2024)

Tsaokoflavanols A1–J1: Flavanol-fatty alcohol hybrids with HPL inhibitory activity from Amomum tsao-ko - Tian-Rong Yang; Shi-Chao Huang; Yun-Fen Wang; Zai-Xiang Lou; Shao-Xing Dai; Li-Hua Su; Min Xu (Phytochemistry, 2024)

Green space and its types can attenuate the associations of PM2.5 and its components with prediabetes and diabetes—— a multicenter cross-sectional study from eastern China - Zhiqian Cui; Rubing Pan; Jintao Liu; Weizhuo Yi; Yuxin Huang; Ming Li; Zichen Zhang; Lingmei Kuang; Li Liu; Ning Wei; Rong Song; Jiajun Yuan; et al. (Environmental Research, 2024)

Evidence for the transportation of aggregated microplastics in the symplast pathway of oilseed rape roots and their impact on plant growth - Sashuang Rong; Shutao Wang; Hongmei Liu; Yuxin Li; Jia Huang; Wanqing Wang; Bing Han; Shiming Su; Wei Liu (Science of The Total Environment, 2024)

Comparing the mechanisms of syntrophic volatile fatty acids oxidation and methanogenesis recovery from ammonia stress in regular and biochar-assisted anaerobic digestion: Different roads lead to the same goal - Gaojun Wang; Peng Fu; Yan Su; Bo Zhang; Mengyuan Zhang; Qian Li; Jianfeng Zhang; Yu-You Li; Rong Chen (Journal of Environmental Management, 2024)

A study of volatiles of young citrus fruits from four areas based on GC–MS and flash GC e-nose combined with multivariate algorithms - Qian Zhang; Rong Xue; Xi Mei; Lianlin Su; Wei Zhang; Yu Li; Jinguo Xu; Jing Mao; Chunqin Mao; Tulin Lu (Food Research International, 2024)

Enhancing the removal of chlorinated hydrocarbons from groundwater using a new BL5 microorganism with functional CS@ZVI materials - Zhiguo Chen; Wenqing Cao; Yan Li; Jingpeng Song; Yiyun Liu; Juncheng Liu; Rong Zhang; Rongxin Su; He Bai (Journal of Water Process Engineering, 2024)